Financing possibilities of the local governmant - Ace Milenkovski; Sasho Kozuharov; Natasha Ristovska (UTMS Journal of Economics, 2016)
There is a high diversity in the possibility of raising funds for municipalities; in particular the possible sources of revenue for financing the municipalities are high. There are certain ways of financing, which are represented in all municipalities, regardless of their economic structure, the number of people or the country in which there are. But there are certain ways of raising funds that are assigned or may be awarded only to a particular type of municipalities. These ways of funding depend on the geographic location of the municipality, the economic structure of the country, available natural resources in the municipality, the number of residents, business and economic development of the municipality etc. This paper is based on comparative analysis between possibilities and practices for financing the municipalities in the Republic of Macedonia and the countries in Europe, taking the practices for funding from the following countries: Serbia, Czech Republic, Germany, Slovenia and Bulgaria. The comparative analysis shows similarities and differences in the practice of financing municipalities in Republic of Macedonia and the countries of Europe, and its purpose is to recognize and implement practices for financing the municipalities from European countries in the municipalities of Republic of Macedonia.
Keywords: H71; 330; funding; municipalities; revenues; Macedonia; Europe